Laser-assisted uvulopalatoplasty (LAUP) complications and side effects: a systematic review - Wischhusen, Jeffrey (Nat Sci Sleep, 2019)
Objective: Laser-assisted uvulopalatoplasty (LAUP) has been used as a treatment option for snoring and obstructive sleep apnea for almost three decades. It has been previously reported that some patient’s sleep-disordered breathing worsened following surgery. The aim of this paper is to further elucidate the specific complications of LAUP. Data sources: A systematic search of the electronic databases MEDLINE/PubMed, Google Scholar, and Embase. Review methods: The PRISMA statement was followed. Databases were searched from inception through September 2, 2018. The following search was applied to MEDLINE/PubMed ((laser AND uvul*) OR (LAUP) OR (LAVP) OR (laser AND (apnea OR apnoea OR sleep))). Results: Forty-two studies with a mean follow-up of 16.1 months reported complications on 3,093 total patients who underwent LAUP. The percentages and associated complications of LAUP are as follows: bleeding (2.6%), candidiasis (0.3%), dryness (7.2%), dysgeusia (0.3%), dysosmia (0.2%), globus sensation (8.2%), surgical site infection (1.3%), velopharyngeal (VP) insufficiency (3.9%), and VP stenosis (1.6%). The mean duration of patient-reported pain in studies that reported pain was 11.65 days. Only globus and VP insufficiency had a significant incidence compared with either the general population or the post-oropharyngeal surgery population with relative risks of 1.48 and 2.25, respectively. Overall, there were approximately 26 complications per 100 patients who underwent LAUP. Conclusion: LAUP is associated with a statistically significant rate of VP insufficiency and globus sensation; however, studies lack details of surgical approaches, suggesting that in a population identified as good candidates, a tissue-sparing approach may result in fewer complications.